How prediction markets can save event studies - Erik Snowberg; Justin Wolfers; Eric Zitzewitz (Institute for the Study of Labor (IZA), 2011)
This review paper articulates the relationship between prediction market data and event studies, with a special focus on applications in political economy. Event studies have been used to address a variety of political economy questions - from the economic effects of party control of government to the importance of complex rules in congressional committees. However, the results of event studies are notoriously sensitive to both choices made by researchers and external events. Specifically, event studies will generally produce different results depending on three interrelated things: which event window is chosen, the prior probability assigned to an event at the beginning of the event window, and the presence or absence of other events during the event window. In this paper we show how each of these may bias the results of event studies, and how prediction markets can mitigate these biases.
urn:nbn:de:101:1-201104193273
Keywords: A2; C58; D72; H50; G14; 330; prediction markets; event studies; political economy; Event Study; Prognoseverfahren; Politisches Ziel; Theorie